Endorsement of COVID-19 related misinformation among cancer survivors. Issue 2 (February 2022) - Guidry, Jeanine P.D.; Carlyle, Kellie E.; Miller, Carrie A.; Ksinan, Albert J.; Winn, Robert; Sheppard, Vanessa B.; Fuemmeler, Bernard F.
Abstract: Objectives: To determine whether cancer survivors currently in treatment are more or less likely to endorse COVID-19 related misinformation compared to their counterparts no longer in treatment and those without a cancer history. Methods: We conducted a Qualtrics survey among 897 adults to determine differences in endorsement of COVID-19 misinformation among cancer survivors in active treatment, cancer survivors no longer in treatment, and a control group with no cancer history. Results: Cancer survivors currently undergoing treatment were more likely to believe misinformation related to COVID-19 than those without a cancer history. Least likely to endorse COVID-19 misinformation were cancer survivor no longer in treatment. Conclusion: These results alert healthcare professionals to overall high levels of endorsement of COVID-19 misinformation among cancer survivors on active treatment. Oncologists and other providers working with patients undergoing treatment for cancer should be particularly mindful of the potential elevated beliefs in misinformation among this group. Practical implications: Since patients undergoing cancer treatment seem to be particularly vulnerable to COVID-19 misinformation, oncologists and other healthcare providers working with this patient population should help address patients' concerns about the pandemic and how it relates to their course of treatment. Highlights: Cancer survivors in treatment were more likely to believe COVID-19 misinformation than those without a cancer history. Least likely to endorse COVID-19 misinformation were cancer survivor no longer in treatment. Being male was related to higher endorsement of misinformation, as were younger respondents.